Islamic social capital and accountability for Baitul Mal Wat Tamwil Institutions' sustainable performance - Rahmawati, Rahmawati; Annuar, Hairul Azlan; Ab Rashid, Hafiz Majdi; Siraj, Siti Alawiah (IGI Global Scientific Publishing, 2025)
The purpose of this paper is to attempt to cover the gap in research on Islamic social capital (ISC) applied to Baitul Maal Wat Tamwil institutions (BMTI). The paper explores the types of Islamic social capital (ISC) information considered essential to disclose in annual reports of BMTI by providing empirical evidence of stakeholders' BMTI perceptions. The questionnaires sent to 117 participants to investigate stakeholders' perception of the importance of ISC information disclosed in the annual reports of BMTI. The result shows the importance of ISC information was used factor analysis which examines 36 ISC information proposing to disclose in annual reports of BMTI. Most respondents perceive ISC information is essential to disclose in annual reports of BMTI that enhance the accountability of BMTI to the community and are valued drivers of business' success. This study contributes to the understanding of the importance of social capital disclosure in BMTI annual reports.